An integrated model for the deep structure of the Chyulu Hills volcanic field, Kenya - Novak, O.; Ritter, J. R. R.; Altherr, Rainer; Garasic, Vesnica; Volker, Frank; Kluge, C.; Kaspar, T.; Byrne, G. F.; Sobolev, S. V.; Fuchs, K. (Tectonophysics, 1997)
The Chyulu Hills, a 1.4 Ma B.P. to Holocene volcanic field located about 150 km to the east of the Kenya rift, is one of the few locations on Earth for which detailed geochemical (volcanic rocks), thermobarometric (xenoliths), seismological and gravity data are available. This paper combines these data to achieve an integrated seismic-petrological model for the deep structure of this volcanic field. Results of a wide-angle reflection and refraction experiment reveal an average crustal thickness of 40 km and a thickness of 20 km for the lower crust. Beneath the volcanic field, the crust thickens to about 44 km. In this region a low-velocity body (LVZ) is modelled which extends from about 30 ± 5 km depth to the Moho. The LVZ is characterised by an increased vP/vS-ratio ranging from 1.81 to 1.93 depending on the possible extents of this body. This is in contrast to the surrounding crust where a ratio of only about 1.76 is observed. In the same area, the results of a teleseismic tomography study show a P-wave low-velocity anomaly of −3%. The seismic data can be explained by either an anorthositic body directly above the Moho in the region of the Chyulu Hills or by the presence of partial melt. Directly beneath the Chyulu Hills, a P-wave velocity of 7.9 km/s is determined for the uppermost mantle; this velocity is 0.2-0.3 km/s lower than that of the surrounding mantle region. The teleseismic tomography model suggests a P-wave low-velocity anomaly of −2.5 to −3.5% in the uppermost mantle (<70 km depth). Widespread garnet-bearing pyroxenitic and lherzolitic mantle xenoliths are mostly well equilibrated and suggest an apparent lithospheric thickness of about 105 km. Most garnet-free spinel harzburgitic xenoliths and some garnet pyroxenitic xenoliths were significantly heated before they were sampled and erupted by the host magmas. Heating events lasted for less than 210 ka as indicated by chemical diffusion profiles observed in orthopyroxene grains. It is suggested that heating was caused by stagnating magmas in the uppermost lithospheric mantle. At the same depth P-wave velocity perturbations of the tomographic model show a low-velocity zone directly underneath the youngest part (SE) of the volcanic field. At depths greater than about 70 km, this low-velocity zone is shifted towards the east, away from the volcanic field.
Elektronische Reproduktion der Druck-Ausgabe vom 24. Juli 1998
Gesehen am 22.11.2022